Characterization and testing of cathode materials for high temperature sodium nickel‑ironchloride battery. (15th November 2022) - Frusteri, Leone; Leonardi, Salvatore Gianluca; Samperi, Mario; Antonucci, Vincenzo; D'Urso, Claudia
Abstract: Metal halides are the active cathode ingredients of Na-MeCl2 batteries, which require a fused secondary electrolyte, sodium tetrachloraluminate (NaAlCl4 ), to facilitate the movement of Na + ions within the cathodic material. The sodium‑nickel chloride (Na - NiCl2 ) battery has been extensively investigated as a promising system for large-scale energy storage applications. The growth of Ni and NaCl particles at the cathode during the discharge process is one of the most critical factors that degrade the performance of the Na-NiCl2 battery. The larger the particles of active ingredients, the smaller the active surface available for the electrochemical reaction. Therefore, an excessive growth of Ni and NaCl particles can increase cell polarization resulting from the reduced active area. High current density, high state of charge (SOC) at the end of the charge (EOC) and low Ni/NaCl ratio are the main parameters that can induce a rapid growth of Ni particles. In light of this, novel cathodic mixtures have been studied and manufactured to simultaneously improve battery performance and to develop less expensive, more performing, sustainable, and environmentally friendly materials. Starting from the well-known cathodic material (Na-NiCl2 ), different mixtures have been prepared by replacing nickel with iron (10–90 % substitution). The study of the structural, morphological and physico-chemical properties of the prepared materials was carried out, together with their characterization as cathode materials for sodium-metal halide battery. The test cells assembled with the new cathode materials showed excellent specific capacity and energy values up to 123 mAh g −1 and 275 mWh g −1 (per total Ni-Fe/NaCl weight), respectively. The results have showed that the amount of Ni can be reduced up to 50 % with a parallel increase of the energy storage performance. Highlights: ZEBRA battery is a promising technology for large-scale renewable energy storage. Ni is reduced up to 50 % with a parallel increase of the energy storage performance. Synergic effect of Ni and Fe species improves the utilization of the cathode mass.